Safety of subcutaneous immunotherapy with Novo-Helisen-Depot in the children: a retrospective analysis from a single center in Northern China - Zhou, Qianlan; Liu, Si; Dai, Bing; Chen, Li; Han, Lina; Zhang, Qinzhen; Shen, Wenxin; Shan, Lishen (Frontiers in Pediatrics, 2024)
Little is known about The safety of mite extract product Novo-Helisen Depot (NHD) as subcutaneous immunotherapy (SCIT) in the children with mite allergy especially immediate/late local reaction (LRs).We conducted a retrospective study analyzing the adverse events of the children undergoing subcutaneous immunotherapy with NHD. Adverse events included local and systemic adverse reactions (SRs) at the very early and late stage. The correlation of the basic characteristics, laboratory analysis results, LRs and SRs were analyzed. Results: Two hundred and eighty-seven patients received at least 15 months of subcutaneous immunotherapy with NHD were included in the analysis. Skin-prick testing (SPT) results of D.pteronyssinus was associated with an increased risk of immediate LRs in build-up phase (OR =1.53, 95% CI: 1.02,2.37) and delayed LRs in maintenance phase (OR =1.58, 95% CI: 1.05,2.46), while SPT results of D. farinae was associated with an increased risk of SRs (OR =3.22, 95% CI:1.17,10.00) and severe SRs (OR =7.68, 95% CI: 1.13,109.50). Serum IgE level of D. pteronyssinus was associated with an increased risk of SRs (OR =1.01, 95% CI: 1.00,1.03). Patients with both asthma and allergic rhinitis was associated with an increased risk of SR, and severe SRs (P<0.05).NHD as SCIT is safe. The children with higher SPT level with D. farinae or D. pteronyssinus, higher serum IgE level of D. pteronyssinus, children with both asthma and allergic rhinitis, and the children with treatment interruption had higher risk of adverse events.